PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SISWA SMA NEGERI 5 YOGYAKARTA - Heri Kurnia; Joko Wahono (Academy of Education Journal, 2021)
This study aims to determine the effect of emotional intelligence on the learning achievement of Pancasila education and citizenship of students at SMA Negeri 5 Yogyakarta in the 2019/2020 academic year. This research is a quantitative descriptive study, the data collected is in the form of quantitative data (PPKn learning achievement or report cards) and data qualitative quantified (emotional intelligence), this research was conducted at SMA Negeri 5 Yogykarta in March 2020. Number of samples in this study were 720 respondents, with details of class X having 8 classes, class XI there are 8 classes and class XII there are 8 classes, so there are a total of 24 classes. Of the 24 classes (from each class) a sample of 30 students was taken using simple random sampling technique. Data obtained from questionnaires are then processed by a simple regression analysis and coefficient of determination (R2). For the data on emotional intelligence (X), the researchers took the data by distributing questionnaires, while the students' learning achievement scores for Pancasila and Citizenship Education (Y) were the final grades (report cards) in the even semester of the 2019/2020 school year. The results showed: statistical analysis. produces a regression equation Y = 74.298 + 0.165 X, meaning that if the value of emotional intelligence (X) increases by 1 unit, the learning achievement value of PPKn (Y) will increase by 0.165 units with a constant value of 74,298. Hypothesis testing shows that the independent variable emotional intelligence is proven to significantly affect the dependent learning achievement of PPKn. The coefficient of determination (R2) obtained was 0.59 (5.9%), meaning that the variable has an influence emotional intelligence contributes 5.9% to the achievement variable learn PPKn and 94.1% are influenced by other factors outside emotional intelligence variable.